The Problems and Practicalities of Conducting Research on Libraries in a Conflict Zone - Miller, Rebecca L. (Qualitative and Quantitative Methods in Libraries, 2019)
Conducting research in a conflict zone poses its own particular set of problems to overcome. This paper presents the experience of the author in conducting a survey of librirares in Afghanistan. Challenges such as translation of the survey, identifying and reaching participants, and other practical matters in the cultural context of Afghanistan are discussed. Based on this study and previous research experience in Afghanistan, suggestions are offered for managing future research endeavors on libraries and access to information in Afghanistan, including the feasibility of random selection. Finally, these challenges and suggestions are brought into the larger picture of research conducted in conflict zones more generally.